Thickened Retinal Nerve Fiber Layers Associated With High-Altitude Headache - Yin, Xianhong; Li, Yi; Ma, Yanyun; Xie, Yuan; Wang, Kun; Sun, Dayan; Liu, Xiaoyu; Hao, Meng; Liang, Meng; Zhang, Shixuan; Guo, Yuan; Jin, Li; et al. (Frontiers in Physiology, 2022)
Abstract Purpose: The study aimed to quantify the different quadrants of optic nerve head (ONH) and macular parameters and its changes during exposure to high altitude and to assess a correlation with high-altitude headache (HAH). Methods: Spectral domain optical coherence tomography was used to quantify changes of retinal structure in 109 healthy subjects during acute exposure to high altitude (3700 m). Self-reported symptoms of HAH and AMS were assessed using Lake Louise Score (LLS), alongside measurements of physiological parameters (oxygen saturation (SpO2), heart rate (HR), hemoglobin (Hb) and red blood cells (RBC). Measurements were taken before and after exposure to the high-altitude environment. These parameters were used to correlate with changes at the ONH and macula. Results: Exposing to high altitude, incidence of AMS was 43.6% and occurrence of HAH was 66.97% (54.13% mild, 12.84% moderate-severe). For systemic parameters measured at high altitude, participants exhibited significantly lower SpO2, higher resting HR, higher Hb and higher RBC (all P < 0.05). Key stereometric parameters used to describe ONH (superior, inferior, nasal, temporal and mean retinal nerve fiber layer [RNFL] thickness) and macula (macular thickness) increased at high altitude compared to baseline. Most parameters of ONH changed, especially in superior, inferior and mean RNFL thickness (P < 0.05). There was significant correlation between ratios of RNFL in ONH and HAH [mean thickness (r = 0.205, P = 0.03); inferior (r = 0.216, P = 0.02) and nasal (r = 0.193, P = 0.04)]. No association between parameters of ONH and AMS or LLS was observed. Conclusions: The high-altitude environment can increase RNFL thickness in the ONH. Furthermore, we found that ratios of mean thickness, inferior area and nasal area correlate positively with HAH which provide new insights for understanding the underlying pathological mechanisms of high altitude retinopathy (HAR). Keywords:high altitude, headache, high-altitude headache, OCT, retinal nerve fiber layer, RNFL